The Effectiveness of the Learning Model Oriented Towards the Dimensions of Knowledge and Cognitive Processes - Widiana, I Wayan; Rendra, Ndara Tanggu (LPPM Undiksha, 2020)
The teachers in elementary schools have not conducted studies and developments as well as changes in the learning process oriented towards the latest student cognitive domains. The proof is that the teacher is only able to make items on the evaluation of learning outcomes that only ask students to utter memorization. This study aims to develop a learning model oriented to the dimensions of knowledge and cognitive processes. This type of research is a development with the Dick & Carey model. The subject of this research is a learning model oriented to the dimensions of knowledge and cognitive processes. Data collection methods used were interviews, documentation, questionnaires, and tests. The data analysis used is the t-test. The results showed that the learning model with the orientation of knowledge and cognitive processes (PSBDPPK) was valid, effective, and efficient to be applied in elementary schools, and the results of the t-test show that this model has a significant effect on student learning outcomes, this is indicated by the t-test, the value (Sig. (2-tailed)) is 0,000. So, it can be concluded that the learning model that crosses the dimensions of knowledge and cognitive processes (PSBDPPK) is valid, effective, and efficient to be applied in elementary schools.